Охранные исследования на городище Вилино в 2009 г. - Пуздровский, А.Е.; Медведев, Г.В.; Ляшук, П.М. (Археологічні дослідження в Україні, 2010)
Protective archaeological research at the Ancient Greek and Scythian hill-fort Viline in Bakhchisaray Region of the Crimea are highlighted. Three horizons of site existence were discovered: from the end of the 4th c. to the beginning of the 3rd c. BC, from the end of the 3rd c. to the beginning of the 2nd c. BC, and from the end of the 2nd c. BC to the 1st c. AD.